'Gallagher' and 'Iba' hard red winter wheat: Half‐sibs inseparable by yield gain, separable by producer preference. Issue 1 (26th January 2021) - Marburger, David A.; Silva, Amanda de Oliveira; Hunger, Robert M.; Edwards, Jeffrey T.; Van der Laan, Liza; Blakey, Adrienne M.; Kan, C‐C.; Garland‐Campbell, K.A.; Bowden, Robert L.; Yan, Liuling; Tilley, Michael; Chen, Ming‐Shun; et al.
Abstract: Cornerstone cultivars earn their status as much by their genetic fortitude and successive progeny as by their own visibility. 'Duster' hard red winter (HRW) wheat ( Triticum aestivum L.) established a foundation of yield potential, pest resistance, and baking quality on which two half‐sib progenies named 'Gallagher' (Reg. no. CV‐1177, PI 667569) and 'Iba' (Reg. no. CV‐1178, PI 667570) were released by the Oklahoma Agricultural Experiment Station in 2012 and subsequently assumed significant commercial hectares in the U.S. southern plains. Our objectives were to characterize and compare Gallagher and Iba with their parent Duster for a wide array of agronomic, end‐use quality, and wheat sensitivity traits. Bulked descendants of sister F4:5 lines, Gallagher and Iba were tested as experimental lines OK07214 and OK07209, respectively. In one breeding cycle, they showed an 8% yield gain in grain‐only environments, with 10–17% increases in kernel weight, divergent wheat protein responses, unidirectional responses in total fructan content, and wide bidirectional responses in flour levels of immunotoxic gluten epitopes. Both cultivars remain excellent sources of yield potential and functionality, yet their ultimate adoption histories did not align with institutional expectations at the time of release. This retrospective analysis provides a non‐abstract reminder worthwhile for any agent of wheat improvement: wheat producers may exercise cultivar choice on seemingly modest characteristics but with yield‐equivalent precedence.